2016
DOI: 10.20524/aog.2016.0085
|View full text |Cite
|
Sign up to set email alerts
|

Oral steroid prophylaxis is effective in preventing esophageal strictures after large endoscopic resection

Abstract: BackgroundStrictures are frequent complications of large endoscopic mucosal resections (EMR) and endoscopic submucosal dissections of the esophagus. Local or systemic steroid therapy has shown promise in the prevention of secondary stenosis. The aim of this study was to evaluate the safety and efficacy of systemic steroid therapy following endoscopic resection of at least hemi-circumferential esophageal mucosa.MethodsThis was a single-center retrospective study in a tertiary center. We evaluated patients who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Ratone et al reported a 13% stricture rate using Yamaguchi's regime in 31 patients. However, he included resection ulcers exceeding 50% that makes interpretation of the data difficult [17]. Today, local injection of triamcinolone into the resection ulcer immediately after ESD is the preferred treatment strategy in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Ratone et al reported a 13% stricture rate using Yamaguchi's regime in 31 patients. However, he included resection ulcers exceeding 50% that makes interpretation of the data difficult [17]. Today, local injection of triamcinolone into the resection ulcer immediately after ESD is the preferred treatment strategy in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…When the lesion area is large enough, the artificial esophageal ulcer causes excess absence of epithelial cells and results in fibrous repair in the submucosa[ 27 ], which is the primary cause of esophageal stricture. To prevent esophageal stricture, the administration of steroids is useful, as previously reported[ 28 , 29 ], while endoscopic balloon dilation and esophageal stent implantation can also be options[ 30 , 31 ]. For positive margin, previous studies reported its incidence after ESD to be 3%-17%[ 18 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce this risk, high-risk patients may benefit from post-procedure steroid injection or oral corticosteroid therapy. 68,69 Ablative therapies, especially RFA, can also pose risks to the development of strictures. After EMR, ESD and ablative treatment, patients should receive high-dose proton pump therapy to mitigate stricture formation, following evidence of its use in reflux esophagitis.…”
Section: Stricture Formation Following Be Endotherapymentioning
confidence: 99%
“…In situations where the EMR or ESD dissection circumference is >75% or craniocaudal resection length over 40 mm, the risk of developing a symptomatic stricture is up to 50%. To reduce this risk, high‐risk patients may benefit from post‐procedure steroid injection or oral corticosteroid therapy 68,69 . Ablative therapies, especially RFA, can also pose risks to the development of strictures.…”
Section: Stricture Formation Following Be Endotherapymentioning
confidence: 99%